Ministerial Decree No.10/2006 Promulgating The Executive Regulations of the Customs Law No. 66/1963 = اللائحة التنفيذية لقانون الجمارك / Minister Prime - Egypt. Minister Prime (2025)
1. customs control and distinctive elements of goods -- 2. customs procedures -- 3. special customs systems -- 4. Arbitration -- 5. customs officials